환경친화성 경질 3가 크롬도금의 연구동향 - 김만(M. Kim); 이종재(J.J. Lee); 김대영(D.Y. Kim); 박상언(S.U. Park); 권식철(S.C. Kwon) (Biuletyn Uniejowski, 2004)
Hard chromium coating technology using hexavalent chromium bath is widely used in various industries. Because of the serious health and environmental problems of hexavalent chromium, many attempts to alternate the hexavalent chromium plating have been made over 50 years. Trivalent chromium plating is one of the challengeable technologies to alternate hexavalent chromium plating. It is relatively none-toxic. Although some papers have described hard chromium coatings produced from trivalent chromium solution, it has limited the industrialization because of chemical and electrochemical problems of trivalent chromium ions. This paper introduces a number of factors for successful trivalent chromium plating, to give a some information about trivalent chromium process.